228k views
0 votes
Write the expression as a single natural logarithm

3 ln a - 1/2(ln b + ln c^2)

Can you show me how you got it please?

1 Answer

3 votes
rules
1)ln a+ln b=ln(a+b)
2) x ln(a)= ln(a)^x
3) ln(a) -jn(b) =ln (a/b)

so,
1) ln b + ln c^2 =ln(b/c²)
so, 3 ln a - 1/2(ln b + ln c^2)=3 ln a - 1/2ln(b/c²) = 3 ln a - ln(b/c²)^1/2 =

3 ln a - ln(b/c²)^1/2 =ln a³ - ln(b/c²)^1/2 = ln a³ - ln ((b^(1/2)/(c²)^(1/2))=
= ln a³ - ln ((b^(1/2))/c) = ln ( a³ /((b^(1/2))/c) )= ln ( (a³ c)/(b^(1/2))
User Koffiman
by
5.5k points